Nutritional Impact on the Productivity of Ready-Made Garment Workers - Islam (Rajib), Md. Monirul; Nadila, Farjana Tasnim; Arpa, Tasnia Quamar; Arefin, Md. Shafiul; Popy, Tarana Haque; Emon, Proshun Chowdhury (European Scientific Journal, ESJ, 2023)
This study shows the gradual increment in apparel productivity after feeding some nutrients to selected sewing operators who work in a factory named Daarkak, in the urban area of Dhaka, Bangladesh. The specific objective was to identify the consequences of nutritious food in boosting workers’ energy levels to aid in increased productivity. A better result compared to the previous data was found, where the productivity increased substantially after providing selected nutritious food- soya and milk. The overall result was impressive. Since most of the workers belong to the low-middle class or poor families, they do not afford nutritious food in daily life for the lack of knowledge that nutritious food can be availed at cheaper prices. Soya and milk contain adequate proteins and they are available at relatively cheaper costs. These foods enabled them mentally and physically to give higher efficiency during their regular work. This paper explores the possibility of improved productivity after providing workers with nutritious food. When productivity increases, profit also increases.